Health Care and Mortality among Persons with Severe Mental Illness: A Case-Control Epidemiological Study. (April 2017) - Gal, Gilad; Munitz, Hanan; Levav, Itzhak
Objective: Reports show disparities in the health care of persons with severe mental illness (SMI), including in countries with universal health insurance. However, the moderating effect on disparities of specific mental health legislation is yet to be studied. The study aimed to investigate equality of health care for people with SMI in a country with a national health insurance and a comprehensive rehabilitation law for persons with mental disabilities. Method: A case-control epidemiological study compared health services (laboratory tests, visits to specialists, and medications) provided to users with and without a history of schizophrenia and bipolar disorder ( N = 52, 131) and with regard to a subgroup of users with diabetes ( n = 16, 280). In addition, we examined the mortality rates of the study population. Results: While service users with schizophrenia were somewhat less likely to meet the same indexes of care as controls, those with bipolar disorder did not differ from their counterparts. Yet, mortality risk among service users with schizophrenia and bipolar disorder was 2.4 and 1.7 times higher, respectively. Rates of services to persons with SMI and comorbid diabetes did not differ from their counterparts. Conclusions: In Israel, a country with a national health insurance and a rehabilitation law for persons with mental disabilities, service users with bipolar disorder receive equitable levels of general health care. For users with schizophrenia, the disparities exist in some of the health care measures but to a smaller extent than in other countries with universal health insurance. In contrast, mortality rates are elevated in persons with SMI.